Research into the relationship between digital health literacy and healthy lifestyle behaviors: an intergenerational comparison - Çetin, Murat; Gümüş, Rojan (Frontiers in Public Health, 2023)
Introduction Digital health literacy wields a pivotal role in individuals’ health status in terms of seeking and choosing appropriate and accurate information, and useful services from a vast array of choices. This study is aimed at assessing the validity and reliability of the Turkish version of Digital Health Literacy Instrument (DHLI) and examining the relationship between DHL and the healthy lifestyle behaviors of participants from X, Y, and Z generations. Methods In this study, to conduct a cross-sectional web-based survey, an online self-report questionnaire was built, and a convenience sample with a snowball approach was used. The study was conducted among 1,274 respondents aged between 18 and 64 years. Data collection tools consisted of the Personal Information Form, Lifestyle Behavior Scale II (HLBS II), and DHLI. Cultural validation and psychometric testing of DHLI, exploratory factor analysis, confirmatory factor analysis, Cronbach’s alpha test, and bivariate and multivariate regression analysis were used for statistical analysis. Results In the study, the Turkish version of the DHLI tool consisting of six dimensions proved to be valid and reliable, and deemed appropriate for use across all age groups. The average digital health literacy of the respondents was sufficient, but the mean of healthy lifestyle behavior scores was moderate. There was a positive significant relationship between the total mean scores of DHLI and HLBS. Among the subdimensions of DHLI, while the highest mean scores were in DHLI Reliability, DHLI Privacy, and DHLI Search, DHLI Navigation and DHLI Relevance showed the lowest mean scores. DHLI Reliability, DHLI Relevance, and DHLI Adding Content were statistically significant predictors of health-related behaviors of the respondents. Conclusion The most important feature and novelty of this study is that, although the DHLI scale has been widely translated for use in many countries, it has been translated and adapted to Turkish for the first time herein. The study offers crucial evidence about Generation X, Y, and Z’s DHL level and its positive relationships with health-related behaviors. Therefore, the community and its partners should lead the way in empowering individuals to understand and use online information in an effective, secure, and health-promoting manner, along with governments.